Kinetic and Spectroscopic Studies of Aerobic Copper(II)-Catalyzed Methoxylation of Arylboronic Esters and Insights into Aryl Transmetalation to Copper(II) - King, Amanda E (Organometallics, 2012)
We previously reported a preliminary mechanistic study of aerobic Cu(OAc)(2)-catalyzed methoxylation of 4-tolylboronic ester (King, et al. J. Am. Chem. Soc., 2009, 131, 5044-5045), which revealed that aryl transmetalation from the boronic ester to Cu(II) is the turnover-limiting step. In the present study, more-thorough kinetic and spectroscopic studies provide additional insights into transmetalation pathway and the identity of the Cu(II) catalyst resting state(s). EPR spectroscopic studies show that at least two copper(II) species are present under catalytic conditions and their relative populations vary as a function of reaction time and acidity of the arylboronic ester, and are influenced by addition of acetic acid or acetate to the reaction mixture. Analysis of kinetic data and (11)B NMR and EPR spectra under diverse reaction conditions suggests that aryl transmetalation occurs from a tetracoordinate, anionic boronate to a cationic Cu(II) species, mediated by a methoxide-bridge